School-Based Management Practices as Predictors of School Performance in Public Elementary Schools amid the Pandemic - Capacite, Raymund D. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The CoVid-19 pandemic forced a majority of business sectors and government institutions, including the Department of Education to a distance and virtual approach on its mandates. However, it is highly expected that the quality of educational outcomes should be continuously delivered among the stakeholders. Hence, a correlational research design was employed to investigate the level of practice on school-based management and the performance levels of 26 public central elementary schools via secondary data collected from the Schools Governance Operation Division (SGOD), specifically in the implementation of distance education during the school year 2020-2021. The data were analyzed using mean, percentage, Pearson R, and multiple regression analysis at a .05 level of significance. Findings revealed a better level of practice and a good level of performance concerning school-based management (SBM) among participating schools. Likewise, a significant relationship and predictability among the two variables were established, suggesting the influential nature of school-based management in improving the schools’ performance outcomes. Hence, it recommends the benchmarking and implementation of outstanding school-based management practices amid the pandemic across all schools.